Can the mean platelet volume be a predictor of disease activity in primary Sjogren syndrome? - Omma, Ahmet; Kucuksahin, Orhan; Sandikci, Sevinc Can; Ozdemir, Bahar; Erten, Sukran; Karaaslan, Yasar (International Journal of Research in Medical Sciences, 2016)
Background: Disease activity in primary Sjogren syndrome (PSS) is measured by the EULAR Sjogren’s syndrome disease activity index (ESSDAI) and patient reported index (ESSPRI). Studies investigating the association between ESSDAI and ESSPRI and previously reported indicators of systemic inflammation are few in the literature. The aim of this study was to determine the clinical utility of the mean platelet volume (MPV) in predicting disease activity in PSS patients. Methods: A total of 190 subjects including ninety-five PSS patients and ninety-five healthy controls were enrolled. Associations between MPV and other known indicators of systemic inflammation (red cell distribution width (RDW), neutrophil to lymphocyte ratio (NLR) and patient clinical characteristic, ESSDAI and ESSPRI were investigated by using spearman correlation and linear regression analysis. Results: MPV levels were found to be significantly higher in the PSS group than the control group (10.5±1.2 versus 9.0±1; P<0.001 respectively). Correlation and regression analysis showed a positive correlation between MPV levels and ESSDAI scores (r=0.24, p=0.01). There was a negative correlation between ESSPRI and MPV levels (r=-0.32, p=0.001). NLR and RDW did not show any significant correlation with either ESSDAI or ESSPRI scores. Conclusions: MPV levels are significantly elevated in PSS patients compared to their control peers, positively correlate with ESSDAI but negatively with ESSPRI scores. MPV might be a useful inflammatory marker to measure disease activity in PSS.